The Purpose of Support in the Exercise of Legal Capacity: Article 12 at a Crossroads - Broström, Linus; Nilsson, Anna ; 0000-0002-4738-1790; Fridström Montoya, Therése (Scandinavian Journal of Disability Research, 2025)
Article 12 of the UN Convention on the Rights of Persons with Disabilities requires states parties to take appropriate measures to ensure that persons with disabilities have access to the support they may need in exercising their legal capacity. However, this obligation remains ambiguous. What exactly is decision-making support meant to accomplish? Until this fundamental issue has been clarified, policymakers and support persons are left without clear guidelines on what the Convention requires of them. And without clarification of the purpose of Article 12 support, it will not only be impossible to assess the adequacy of any given support arrangement, but also to make informed suggestions about appropriate research and reform agendas. The paper identifies key candidate purposes of support and illustrates how the choice between them has various implications.
Keywords: Human rights; Mänskliga rättigheter